Mikromuovin määrä ja laatu kompostissa ja kierrätyslannoitteessa - Risku, Noora (2023)
Microplastics are a significant environmental problem and have been intensively studied in recent years. One way for them to enter the environment is organic fertilizers made from waste. Organic fertilizer Putretti is made from ash and dry compost from Labio Oy. It is more environmentally friendly to produce than syn- thetic fertilizers and it has a balanced nutrient content. It is planned to be used as a forest fertilizer. In this study I focused on how much plastic particles and what type of plastics Putretti and the compost contain. I used enzymatic degradation to break down the organic compounds and Raman-spectroscopy to identify the plastics (particle sizes found were 15 μm - 6 mm). Fertilizer without added ash and the ready compost material had the highest numbers of plastic particles (299 ± 209 /g wet weight and 273 ± 106 particles/ g, respectively). Particle sizes were biggest before thermal sanitization and smallest in the final product, Putretti. Most of the found particles were polyethylene terephthalate (PET) which is widely used in food packaging. From all particles PET’s proportion was 84 %. From all samples 8 different plastic types were found. There is no legislation for microplastics concentration in organic fertilizers, but a maximum of 0,5 % from products weight can be “trash” (>2 mm particles). In this study, Putretti contained plastic 1,29 % of its wet weight. Counting only bigger particles (> 1 mm), the proportion of plastics is significantly lower (0,001 %), as most of the found particles were < 500 μm. Biowaste from grocery stores comes in their original packaging to composting facility. This study highlights that biowaste treatment cannot remove those plastic packages effectively, so the plastic is transported through the processing into the end product. These results also indicate that plastic waste is fragmented to smaller particles in the composting process.